TIKTOK SEBAGAI SUMBER INFORMASI PEMILIH PEMULA PADA PEMILIHAN KEPALA DAERAH (PILKADA) TAHUN 2024 - Megi Primagara; Neni Yulianita (CV. Denasya Smart Publisher, 2024)
Voters in the 17-21 age group in the 2024 Regional Head Elections (Pilkada) tend to use TikTok as a source of information. This is related to the presence of social media as new media. Dennis McQuail explains that new media is information and communication technology with a related social context that brings together three elements; technological tools and artifacts; activities, practices, and uses and the social order and organisation formed around these tools and practices. The research method uses a literature study with an emphasis on searching documents and online data. The results show that political communication elements consist of political actors, society, and political communication media. Political actors will utilise the media to spread messages to the public, including using TikTok. The selection of TikTok because it is a social media that presents short-duration visuals and is packed with interesting visual effects and music and the content is packed with easy language. With these features, the message of political actors delivered through TikTok can be more easily remembered by novice voters. So that it can help political actors to build public support and opinion.